Faktor kesopanan dan strategi komunikasi dalam genre perbincangan di televisyen - Mashudi, Rohaidah; Musanif, Ahmad Mahmood; Abdul Aziz, Adi Yasran; Mohamad, Hasnah (Penerbit Universiti Kebangsaan Malaysia, 2013)
The interactive nature of discussion programme on television is categorized as a genre based on several identified criteria in accordance to the linguistic genre analysis. In addition, the prominent language usage indicator in the discussion genre on television channels are evidence of a speech event. The speech event of a discussion on television has created a two-way interaction among the participants. Consequently, the existing social process requires a thorough examination of factors which influence politeness and communication strategy used by the participants. Communication strategies, which are connected to politeness, need to be marked by several factors, which among others are role and differences in social status. The denial of the influence of politeness factors and violation of communication strategies will only result in the participant’s confusion on their understanding of a culture and its society. This research focuses on the discussion genre which is aired on the prime channel, TV 1, on Malaysia Radio and Television broadcasting (RTM). Thorough examination on the use of politeness factors and communication strategies which occur in this speech event have been conducted and data has been analysed and described according to the approach by Asmah Hj Omar. The objective of this study is to explain and describe factors that influence the use of communication strategies marked with politeness, in a television discussion genre. Three episodes based on Forum Hal Ehwal Islam, which discuss religious issues, were recorded. This study found that continuous communication strategies marked with politeness create effective communication in achieving the actual purpose of a discussion aired on television.